Comparison of Traditional lecture and Interactive Teaching Methods in Large Group Teaching of Non Communicable Diseases- A Quasi Experimental Study - Sudha Bala; Surendra Babu; Shrikanth Muralidharan; Mary Moses. P; Nayana K. Hashilkar; Shilpa Bhimalli (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Lectures as a method of teaching are very common and also under increasing criticism due to passive recipients of information with no development of thinking skills or change in attitude. Objectives: To Compare traditional lecture method with interactive teaching methods in large groups and to assess the perceptions of students towards these methods. Material and Methods: A Quasi-Experimental Study was taken up at the Department of Community Medicine among 7th semester students of MBBS course of our Medical College located at Hyderabad for a period of 4 months. Four different teaching-learning methods such as traditional, case-based, Jigsaw, and Quiz were conducted for 4 topics of Non-communicable diseases which were evaluated through objective structured questions and subjective by perceptions rated on a Likert scale(1-5). Results: Out of 100 students, 92 students regularly attended all the teaching methods of 4 topics-Hypertension, Diabetes Mellitus, Stroke, and Coronary artery disease. The highest objective structured mean score of 6.34+2.367 was obtained for case based teaching in hypertension topic, Diabetes Mellitus (6.63+1.827) for the jigsaw method, Coronary artery disease (6.95+1.561) and stroke (6.11+1.941). Subjective rating was excellent for jigsaw method in context with the topic related to Hypertension and stroke. Quiz was rated as excellent for the topics related to Diabetes mellitus and Coronary artery disease. For the overall perceptions consisting of positive and negative questions, highest score was rated for the jigsaw method of teaching. Conclusions: Objective evaluation has revealed higher scores with interactive teaching methods compared to traditional method and on students feedback about their perceptions and most preferable method, the jigsaw scored the highest.